2011
DOI: 10.1002/ppul.21545
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath temperature and exercise‐induced bronchoconstriction in asthmatic children

Abstract: It has been hypothesized that exhaled breath temperature (EBT) is related to the degree of airway inflammation/remodeling in asthma. The purpose of this study was to evaluate the relationship between the level of airway response to exercise and EBT in a group of controlled or partly controlled asthmatic children. Fifty asthmatic children underwent measurements of EBT before and after a standardized exercise test. EBT was 32.92 ± 1.13 and 33.35 ± 0.95°C before and after exercise, respectively (P < 0.001). The %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…In a previous study, we found that an increase in EBT correlated with a decrease in forced expiratory volume in 1 s (FEV 1 ) in both asthmatics and controls after an exercise challenge test [11]. A similar correlation has been found in asthmatic children [12]. In addition, we found that there was a prolonged increase in EBT after exercise in asthmatics for whom the FEV 1 fell during the test compared to asthmatic subjects for whom it did not fall.…”
Section: Introductionsupporting
confidence: 51%
“…In a previous study, we found that an increase in EBT correlated with a decrease in forced expiratory volume in 1 s (FEV 1 ) in both asthmatics and controls after an exercise challenge test [11]. A similar correlation has been found in asthmatic children [12]. In addition, we found that there was a prolonged increase in EBT after exercise in asthmatics for whom the FEV 1 fell during the test compared to asthmatic subjects for whom it did not fall.…”
Section: Introductionsupporting
confidence: 51%
“…Previous studies have shown discrepant results regarding this association. Peroni et al [21] found no correlation with EBTp in 50 children with asthma treated with ICS after exercise-induced bronchoconstriction, while in asthmatic children not treated with ICS they found an increase in EBTp and a decrease in FEV 1 after the same exercise. Svensson et al [22] did not find changes in EBTp in asthma patients before or after two bronchoconstriction tests (eucapnic voluntary hyperventilation and methacholine challenge).…”
Section: Discussionmentioning
confidence: 99%
“…It is increased in persistent asthmatics and correlate with other markers of local inflammation (FENO and FEV1) [21,22]. However, we found a low to moderate correlation between frequency of asthma symptoms and local inflammation presented with EBT.…”
Section: Discussionmentioning
confidence: 50%